Social familiarity modulates personality trait in a cichlid fish - Galhardo, Leonor (2020)
Personality traits, such as exploration-avoidance, are expected to be adaptive in a given context (e.g. low-risk environment) but to be maladaptive in others (e.g. high-risk environment). Therefore, it is expected that personality traits are flexible and respond to environmental fluctuations, given that consistency across different contexts is maintained, so that the relative individual responses in relation to others remains the same (i.e. although the magnitude of the response varies the differences between high and low responders are kept). Here, we tested the response of male cichlid fish (Oreochromis mossambicus) to a novel object (NO) in three different social contexts: (i) social isolation, (ii) in the presence of an unfamiliar conspecific, and (iii) in the presence of a familiar conspecific. Males in the familiar treatment exhibited more exploratory behaviour and less neophobia than males in either the unfamiliar or the social isolation treatments. However, there were no overall correlations in individual behaviour across the three treatments, suggesting a lack of consistency in exploration-avoidance as measured by the NO test in this species. Moreover, there were no differences in cortisol responsiveness to an acute stressor between the three treatments. Together, these results illustrate how behavioural traits usually taken as measures of personality may exhibit significant flexibility and lack the expected consistency across different social contexts.